Pengaruh Kompensasi, Disiplin Kerja Dan Turnover Intetion Terhadap Kinerja Karyawan Koperasi Bina Usaha Kota Bima - Suharni Suharni; Kartin Aprianti (Jurnal Bintang Manajemen, 2023)
This study aims to determine the effect of compensation, work discipline, turnover intention on the performance of employees of the Bima City Business Development Cooperative. The approach used in this research is using an associative approach. The sample in this research is 32 respondents. Data collection techniques used are observation, questionnaires, and literature study. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, coefficients of determination, t tests, and F tests processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results showed that compensation (X1), work discipline (X2) and turnover intention (X3) simultaneously have a significant effect on the performance of employees of the Bima City Business Development Cooperative. with an effect of 66.8%.